2020
DOI: 10.3390/s20154099
|View full text |Cite
|
Sign up to set email alerts
|

Materials Contamination and Indoor Air Pollution Caused by Tar Products and Fungicidal Impregnations: Intervention Research in 2014–2019

Abstract: Construction materials containing tar products are a source of indoor air pollution in buildings. This particularly concerns old buildings, in which wooden structures were impregnated with tar compositions (creosote oil and Xylamite oil containing tar products) and buildings in which bituminous seal containing hydrocarbon solvents was used. During the 1970s and 1980s, an impregnant known as Xylamite was commonly used in Polish buildings. This material still emits organic vapors into the building’s environment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Based on the presented and previous studies [31], the author demonstrated that such compounds as naphthalene, methyl naphthalenes, dimethyl naphthalenes, biphenyl and acenaphthene could be identified in the air, in rooms where tar or asphalt binder was present, and in rooms where the wood was impregnated with chloronaphthalene-based agents [31]. This article [31] provides quantitative and qualitative results, and explains more about the differences between emissions from wooden structures, which were impregnated with tar compositions (creosote oil and Xylamite oil containing tar products), and buildings in which bituminous seal containing hydrocarbon solvents was used. The enumerated compounds seem responsible for the naphthalene-like odour of the air in the rooms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the presented and previous studies [31], the author demonstrated that such compounds as naphthalene, methyl naphthalenes, dimethyl naphthalenes, biphenyl and acenaphthene could be identified in the air, in rooms where tar or asphalt binder was present, and in rooms where the wood was impregnated with chloronaphthalene-based agents [31]. This article [31] provides quantitative and qualitative results, and explains more about the differences between emissions from wooden structures, which were impregnated with tar compositions (creosote oil and Xylamite oil containing tar products), and buildings in which bituminous seal containing hydrocarbon solvents was used. The enumerated compounds seem responsible for the naphthalene-like odour of the air in the rooms.…”
Section: Discussionmentioning
confidence: 99%
“…All the compounds with the mass spectra matching factors p ≥ 80% were regarded as identified. The author described the odour substances according to subjective perception and previous experience [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor air pollution in buildings is associated with the use of technologies, construction products and equipment that can release harmful gases, and vapours such as formaldehyde, toluene, benzene, xylene and others, which are contained in impregnants, paints, varnishes—generally, finishing materials in construction. Specialised indoor-air laboratories can find other toxic substances such as phenol cresols, naphthalenes, chlorophenols, chloronaphthalenes and others 5 . A separate category of harmful outdoor and indoor air contamination is fibrous dust—asbestos.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds include small, solid particles known as particulate matter, which can be classified as PM2.5 (2.5 µm) or PM10 (10 µm) (5). Viruses (6), bacteria, fungi, and inorganic substances such as metal ions, salt, and other solids (7) can all be harbored by airborne PM2.5 particles. Moreover, the small size of PM2.5 particles means they cannot be easily removed through natural inhalation (8).…”
mentioning
confidence: 99%